2020
DOI: 10.3390/infrastructures5040033
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness and Strength Improvement of Geosynthetic-Reinforced Pavement Foundation Using Large-Scale Wheel Test

Abstract: Laboratory cyclic plate load tests are commonly used in the assessment of geosynthetic performance in pavement applications due to the repeatability of testing results and the smaller required testing areas than traditional Accelerated Pavement Testing facilities. While the objective of traditional plate load testing procedure is to closely replicate traffic conditions, the reality is that rolling wheel loads produce different stresses in pavement layers than traditional cyclic plate load tests. This two-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Therefore, proper mix design is recommended before using an excessive amount of RAP. The study by Wright et al [9] aimed to determine the difference in the post-trafficked strength and stiffness of pavement foundation. A dynamic cone penetrometer and light weight deflectometer were utilized to determine material changes from this trafficking and revealed that all specimens that included a geosynthetic layer had a higher base stiffness and strength, while the specimen with geotextile and geogrid in combination created the greatest stiffness and strength after large-scale rolling wheel trafficking.…”
mentioning
confidence: 99%
“…Therefore, proper mix design is recommended before using an excessive amount of RAP. The study by Wright et al [9] aimed to determine the difference in the post-trafficked strength and stiffness of pavement foundation. A dynamic cone penetrometer and light weight deflectometer were utilized to determine material changes from this trafficking and revealed that all specimens that included a geosynthetic layer had a higher base stiffness and strength, while the specimen with geotextile and geogrid in combination created the greatest stiffness and strength after large-scale rolling wheel trafficking.…”
mentioning
confidence: 99%